Methane Adsorption on Graphitic Nanostructures: Every Molecule Counts - Zöttl, Samuel (American Chemical Society, 2012)
[Image: see text] Bundles of single-walled nanotubes are promising candidates for storage of hydrogen, methane, and other hydrogen-rich molecules, but experiments are hindered by nonuniformity of the tubes. We overcome the problem by investigating methane adsorption on aggregates of fullerenes containing up to six C(60); the systems feature adsorption sites similar to those of nanotube bundles. Four different types of adsorption sites are distinguished, namely, registered sites above the carbon hexagons and pentagons, groove sites between adjacent fullerenes, dimple sites between three adjacent fullerenes, and exterior sites. The nature and adsorption energies of the sites in C(60) aggregates are determined by density functional theory and molecular dynamics (MD) simulations. Excellent agreement between experiment and theory is obtained for the adsorption capacity in these sites.